(untitled) (Foro de Educacion, 2016)
In the study of ethics in liberal democracy from the analysis of the «most important moral philosopher of the last century», John Rawls, cataloged by his followers and neo-Kantian, is seen the thin line that crosses the threshold of democracy as a form of government and its purely procedimental, as human actions are reviewed framed in his critique of the dominant ethical currents in American culture of his time, to show their moral and political thought the idea of a well-ordered society «and peaceful society expansionist» lawful and respectful of Human Rights. Rawls comes from its main tenets solve the traditional conflict between equality and freedom democratic from the merely political not metaphysical.